2016
DOI: 10.1007/s13277-016-5041-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for embryonic stem-like signature and epithelial-mesenchymal transition features in the spheroid cells derived from lung adenocarcinoma

Abstract: Identification of the cellular and molecular aspects of lung cancer stem cells (LCSCs) that are suggested to be the main culprit of tumor initiation, maintenance, drug resistance, and relapse is a prerequisite for targeted therapy of lung cancer. In the current study, LCSCs subpopulation of A549 cells was enriched, and after characterization of the spheroid cells, complementary DNA (cDNA) microarray analysis was applied to identify differentially expressed genes (DEGs) between the spheroid and parental cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…In addition, for lung cancer, there is no widespread consensus regarding the best CSC markers. 22 Consequently, "liquid biopsy" has been used for isolation and characterization of CSCs in almost all cancers as it has the potential to be used for frequent genetic analysis of tumor diagnosis/prognosis, in personalized therapy selection and provides considerable leverage of being detected at any tumor stage. [7][8][9]23 CTCs hold much more genetic/molecular information than free-circulating nucleic acid and proteins, thus revealing the importance of inter-cell heterogeneity in correlating cancer prognosis and treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for lung cancer, there is no widespread consensus regarding the best CSC markers. 22 Consequently, "liquid biopsy" has been used for isolation and characterization of CSCs in almost all cancers as it has the potential to be used for frequent genetic analysis of tumor diagnosis/prognosis, in personalized therapy selection and provides considerable leverage of being detected at any tumor stage. [7][8][9]23 CTCs hold much more genetic/molecular information than free-circulating nucleic acid and proteins, thus revealing the importance of inter-cell heterogeneity in correlating cancer prognosis and treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Roudi et al showed indicated loss of CD44 expression and gain of CD24 expression (CD44(−&x41;/CD24(+)) in spheroid cells obtained from A549 cell line. 22 However, these studies were based on tissue samples or cell line, while our study is based on the CTSCs isolated from the peripheral blood of NSCLC adenocarcinoma patients. Conversely, we have found CD44(+)/CD24(−) cells to be able to form larger spheres within a few days, indicative of their ability to undergo cell division due to enhanced self-renewal efficiency which could be perpetuated for many generations.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from MKN-45-miR-31 or the control groups using RNX-plus solution (Cat No. RN7713C, Cin-naGen Inc., Tehran, Iran) using the manufacturer's instructions (23). cDNA synthesis was performed using a kit for mRNA synthesis (Cat No.…”
Section: Rna Extraction Cdna Synthesis and Quantitative Rt-pcrmentioning
confidence: 99%
“…Approximately 7 × 10 5 of single viable cells were plated on poly-HEMA coated cell culture flasks in a serum-free medium. Fresh aliquots of EGF and bFGF were added every other day (21). Following culture for 10-12 days, SDCs were collected by gravity, washed with PBS, and detached with accutase (Sigma-Aldrich, USA), and they were then transferred into the cell culture coated flask to promote further generations.…”
Section: Cell Lines Culture and Sphere Formationmentioning
confidence: 99%